2014
DOI: 10.1080/03650340.2013.874559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sowing dates, seed rates and integrated nutrition on productivity, profitability and nutrient uptake of summer mungbean in Eastern Himalaya

Abstract: A field experiment was carried out in the summer seasons of 2010-2012 at north eastern hilly region of Jharnapani, India, to evaluate the effect of sowing dates, seed rates and integrated nutrition on productivity, profitability and nutrient uptake of summer mungbean. Experimental results revealed that 5th April sown crop recorded significantly higher growth attributes, yield, and economics than 15th April sown crop. This was mainly because of the fact that almost all the yield attributing characters were favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
5
10
0
Order By: Relevance
“…FYM application reduced the loss of nutrients through leaching and made available significant amount of plant nutrients, which created a balancing effect on supply of nitrogen, phosphorus and potassium. Similar results were reported earlier by Kumawat et al, (2009b), Kumar and Kumawat (2014) and Yaduwanshi et al, (2018).…”
Section: Nutrients Uptake By Cropsupporting
confidence: 93%
“…FYM application reduced the loss of nutrients through leaching and made available significant amount of plant nutrients, which created a balancing effect on supply of nitrogen, phosphorus and potassium. Similar results were reported earlier by Kumawat et al, (2009b), Kumar and Kumawat (2014) and Yaduwanshi et al, (2018).…”
Section: Nutrients Uptake By Cropsupporting
confidence: 93%
“…The cumulative effect might be due to supply of nitrogen and phosphorus to the crop and also increased solubilization of mineral phosphates and other nutrients similar observation was recorded by Tanwar, (1997), Kumar et al, (2010) and Kumar and Kumawat (2014). Varying treatments of nutrient management has significant effect on the seed yield, straw yield and harvest index of mungbean (Table 1).…”
Section: Resultssupporting
confidence: 64%
“…Singh et al (2010) studies also reported significant effect of sowing dates and on plant height. These results were supported by Kumar and Kumawat (2014) who reported significant interaction of mung bean in the case of plant height. The significant effect of sowing date and variety on plant height may be due to differences in the growth periods.…”
Section: Harvest Index (%)supporting
confidence: 72%